A yeast assay based on the gilthead sea bream (teleost fish) estrogen receptor ß for monitoring estrogen mimics - Passos, A. L. (2014)
A yeast(Saccharomyces cerevisiae)-based assay was developed and tested with steroids and chemicals (mostly pesticides). The induction of b-galactosidase activity was strictly dependent on the presence of seabream (Sparus aurata) ba estrogen receptor(sbERba) and substances known to have estrogenic activity. 17b-Estradiol (E2) and diethylstilbestrol(DES), both agonists, were most active and the antagonist tamoxifen(TAM)was14-fold less active than E2. Among the chemicals tested bisphenol-A was most active, followed by pentachlorophenol and naphthalene. Ligand-binding assays with recombinant sbERba and sbERa revealed that sbERba binds E2 with 6.5-fold higher affinity than sbERa, confirming the selection of a high sensitive receptor for the yeast assay. DES, ICI182, 780,estrone and TAM had higher relative binding affinity to E2 in sbERa than sbERba, although there was no difference in IC50 for these steroids between the two receptors. These results reveal the use fulness of using they east-based receptor assay for detecting chemical interaction with steroid receptors from contaminated samples.